Mechanisms underlying nonsteroidal antiinflammatory drug-mediated apoptosis - Chan, Timothy A. (The National Academy of Sciences, 1998)
Nonsteroidal antiinflammatory drugs (NSAIDs) can inhibit colorectal tumorigenesis and are among the few agents known to be useful for the chemoprevention of neoplasia. Here, we show that the tumor suppressive effects of NSAIDs are not likely to be related to a reduction in prostaglandins but rather are due to the elevation of the prostaglandin precursor arachidonic acid (AA). NSAID treatment of colon tumor cells results in a dramatic increase in AA that in turn stimulates the conversion of sphingomyelin to ceramide, a known mediator of apoptosis. These results have significant implications for understanding and improving colon cancer chemoprevention.